ANALISIS PENTINGNYA MODEL PEMBELAJARAN BERMAIN PERAN DALAM PENDIDIKAN PANCASILA UNTUK MENINGKATKAN HASIL BELAJAR SISWA DI SD NEGERI MARGAWANGI - Riska Maulidya; Sri Erwini Christine (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study analyzes the effectiveness of the role playing learning model in improving student learning outcomes in the Pancasila Education subject of deliberation material in class 6A of SD Negeri Margawangi, Sukabumi, with 27 students as subjects. A descriptive qualitative approach was used through observation, structured interviews with teachers and students, and questionnaires of essay questions based on Bloom's taxonomy (C1-C5) before and after the intervention. The results showed a significant increase in the lowest score from 60 to 70, the highest from 90 to 95, with 26 students reaching or exceeding KKM 70 (previously only 14 students), supported by value distribution data and testimonials that confirmed the activeness, understanding of Pancasila values, and social character development. The role playing learning model is effective in creating interactive and meaningful learning, in line with the Independent Curriculum, recommended to be applied with supporting media regarding similar material.